Financial Literacy Training: Understanding How to Manage Cash Flow and Plan Business Finances Better in MSMEs in Kembangan Subdistrict - Minanari, Minanari; Yessie, Afly (CV. Proaksara Global Transeduka, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a strategic sector in driving Indonesia's economic growth. However, low financial literacy remains a major challenge in effective business financial management. Based on previous findings, many MSMEs lack sufficient understanding in preparing cash flow statements and systematically planning business finances. This Community Service Activity (PKM) aims to enhance the financial literacy of MSMEs in Kembangan Sub-district through training on cash flow management and business financial planning. The methods employed include interactive lectures, group discussions, and hands-on practice in preparing simple financial reports. The results of the implementation showed an increase in participants' understanding of the importance of financial record-keeping, as well as their ability to create business financial projections. With this improvement, SMEs are expected to be able to manage cash flow more effectively and plan their business finances sustainably.